High resolution seismic refraction data interpretation: an example from Xiakou landslide, Sichuan, China - Pant, Surendra Raj; Li, T.; Wagner, A.; Yi, Fu Wei; Jiaman, Cao (Journal of Nepal Geological Society, 1999)
Among several data processing and interpretation techniques available in seismic refraction, the Generalised Reciprocal Method (GRM) is now widely used. In the thick landslide zone of Xiakou, Sichuan, China, the depths to bedrock obtained from the conventional refraction interpretation by the Plus-Minus Method (Method t0) differed considerably from the results of electrical soundings and drilling. The conventional methods were not able to accommodate to the more likely geological situations (i.e. undetected layers and velocity inversion) in a thick landslide zone. Thicker the overburden more the variation occurred between the results of the GRM and conventional methods. The velocity of seismic waves in the refractor calculated by the Plus-Minus Method was also affected significantly from the bedrock topography. After applying the GRM, the calculated depths were found to be very near to those of the drilling and electrical sounding. The GRM also revealed that the changes in refractor velocity (recorded by conventional methods) were fictitious. The fictitious changes in refractor velocity were caused by the target refractor topography and surface topography. In this paper two profiles are taken for discussion. The profile B-B' represents a case of thick overburden (more than 30 m) whereas the profile D-D' is taken from a thin overburden (less than 15 m) above the target refractor.